Safety of parapulmonal application of xenon in the experiment - V. V. Khinovker; O. F. Veselova; V. A. Koryachkin; E. V. Khinovker; A. A. Gazenkampf (Инновационная медицина Кубани, 2022)
Pain syndrome is the most common reason for patients to seek medical care, the importance of which is steadily increasing in the structure of the total incidence. To optimize costs and ensure high-quality treatment of patients with chronic pain syndrome it is necessary to study existing drugs and methods and introduce new ones. Based on theoretical data on the use of inert gases in medicine, a hypothesis was put forward that xenon could have a pronounced analgesic effect when administered subcutaneously. This study is aimed at confirming the safety of xenon in parapulmonary administration to rats.